Initial Binding of Preproteins Involving the Toc159 Receptor Can Be Bypassed during Protein Import into Chloroplasts - Chen, Kunhua (American Society of Plant Biologists, 2000)
Two integral outer envelope GTPases, Toc34 and Toc86, are proposed to regulate the recognition and translocation of nuclear-encoded preproteins during the early stages of protein import into chloroplasts. Defining the precise roles of Toc86 and Toc34 has been complicated by the inability to distinguish their GTPase activities. Furthermore, the assignment of Toc86 function is rendered equivocal by recent reports suggesting that the standard protocol for the isolation of chloroplasts results in significant proteolysis of Toc86 (B. Bolter, T. May, J. Soll [1998] FEBS Lett 441: 59–62; G. Schatz [1998] Nature 395: 439–440). We demonstrate that Toc86 corresponds to a native protein of 159 kD in pea (Pisum sativum), designated Toc159. We take advantage of the proteolytic sensitivity of Toc159 to selectively remove its 100-kD cytoplasmic GTPase domain and thereby distinguish its activities from other import components. Proteolysis eliminates detectable binding of preproteins at the chloroplast surface, which is consistent with the proposed role of Toc159 as a receptor component. Remarkably, preprotein translocation across the outer membrane can occur in the absence of the Toc159 cytoplasmic domain, suggesting that binding can be bypassed. Translocation remains sensitive to GTP analogs in the absence of the Toc159 GTP-binding domain, providing evidence that Toc34 plays a key role in the regulation of translocation by GTP.